Copyright Ownership of News Content on User Generated Content Based Platforms in Kompasiana - Maulana, Muhammad Asrul; Aristi, Savira (Arena Hukum, 2025)
Unlike previous studies that generally discuss copyright ownership in User-Generated Content (UGC) platforms, this research specifically analyzes the legal implications of Kompasiana’s terms and conditions concerning copyright and economic rights. This normative legal research using a statutory and a conceptual approach. The findings reveal that Kompasiana operates as a UGC platform allowing users to create and share content, such as articles, photos, and comments, while adhering to Indonesian copyright regulations under Law No. 28 of 2014. While Kompasiana’s terms and conditions align with Indonesian laws such as the ITE Law and Copyright Law, concerns remain regarding content creators’ economic rights, particularly when their content is used for promotional purposes without compensation. Terms of use vary depending on the validity of agreements under the legal system of each country, and intellectual property rights over UGC content also differ. This research contributes to legal science by providing a comparative framework applicable to international UGC platforms, emphasizing the necessity for transparent content ownership policies, dispute resolution mechanisms, and economic rights protections. This study offers insights into how different legal systems approach UGC ownership and copyright enforcement, allowing overseas readers to better understand the global implications of digital copyright law. To ensure fairness and legal compliance, Kompasiana should clarify whether users retain full economic rights or if the platform has a non-exclusive license to repurpose content and establish clearer mechanisms for content removal and dispute resolution. This study provides valuable insights into how UGC platforms worldwide can enhance legal transparency and user rights protection.